PERANCANGAN SISTEM POMPA AIR DC DENGAN PLTS 20 kWp TIANYAR TENGAH SEBAGAI SUPLAI DAYA UNTUK MEMENUHI KEBUTUHAN AIR MASYARAKAT BANJAR BUKIT LAMBUH - Bayu Kusuma, Kadek; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2020)
Karangasem Regency, especially in Kubu Subdistrict, Tianyar Tengah Village, Banjar Bukit Lambuh, is an area that still lacks clean water, so that villagers still rely on purchasing clean water through tank trucks at high prices. Around Banjar Bukit Lambuh, there is a 20 kWp Central Tianyar PLTS which has been abandoned since 2016 due to the absence of regional companies that manage and maintain the PLTS so that some components of the PLTS are damaged. The abandonment of the 20 kWp PLTS makes the Bali Provincial Manpower and Energy Department (ESDM) Department plan to transfer the function of PLTS as a source of electricity for water pumps that lift water from reservoirs with a water capacity of 72,000 liters to a 30,000 liter water reservoir which is near the PLTS to meet the water needs of residents in the Middle Tianyar Village Banjar Bukit Lambuh. The selected water pump type Lorentz PS2-4000 C-SJ3-32 submersible DC with a total head of 108.6 meters and a pipe length of 1,640 meters and requires power of 2.96 kW supplied from PLTS 20 kWp Tianyar Tengah with a cable length of 1,640 meters and voltage drop of 8,183 volts, so that the pump can operate for 7 hours with 4.2 m3 / h water discharge producing 29,400 liters of water that can meet the water needs of residents of Banjar Bukit Lambuh Village by 23,328 liters per day.